2015
DOI: 10.1098/rsta.2014.0087
|View full text |Cite
|
Sign up to set email alerts
|

Strategies of symbolization in cardiovascular time series to test individual gestational development in the fetus

Abstract: The analysis of symbolic dynamics applied to physiological time series retrieves dynamical properties of the underlying regulation which are robust against the symbolic transformation. In this study, three different transformations to produce a symbolic series were applied to fetal RR interval series to test whether they reflect individual changes of fetal heart rate variability in the course of pregnancy. Each transformation was applied to 215 heartbeat datasets obtained from 11 fetuses during the second and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 35 publications
0
13
1
Order By: Relevance
“…The present coefficients of determination of P0V%, P1V% and P2V% were lower compared to findings of a previous study (previous study: R 2 > 0.40) (Cysarz et al 2015). The higher coefficients of determination in the previous study were probably caused by two factors: (i) the data sets were shorter (5 min versus 10 min or 30 min), i.e.…”
Section: Binary Symbolic Dynamics Of Fetal Heart Rate In the Course Ocontrasting
confidence: 89%
See 1 more Smart Citation
“…The present coefficients of determination of P0V%, P1V% and P2V% were lower compared to findings of a previous study (previous study: R 2 > 0.40) (Cysarz et al 2015). The higher coefficients of determination in the previous study were probably caused by two factors: (i) the data sets were shorter (5 min versus 10 min or 30 min), i.e.…”
Section: Binary Symbolic Dynamics Of Fetal Heart Rate In the Course Ocontrasting
confidence: 89%
“…fetal heart rate complexity (Van Leeuwen et al 2007). The dynamical features of fetal heart rate vary with GA of the fetus and, hence, the analysis of binary symbolic dynamics reflected changes of fetal cardiac autonomic functioning with progressing age (19th–39th week of gestation) as represented by a strong linear relationship of the measures of symbolic dynamics with GA (Cysarz et al 2015). …”
Section: Binary Symbolic Dynamics Of Fetal Heart Rate In the Course Omentioning
confidence: 99%
“…Legends are included in the text above (TaskForce, 1996) pNN5: percentage of successive NN intervals greater than 5 ms (TaskForce, 1996) HF (high frequency band power) (David et al, 2007) P0V, P1V, P2V: percentage of no, one, or two respective changes in a binary series of successive NN intervals (Cysarz et al, 2015;Cysarz et al, 2013) DCsl1, DCst1, ACsl1, ACst1: Slope and step values of heart rate Deceleration and Acceleration Capacity across 1 NN interval change (short) after PRSA (Phase Rectified Signal Averaging) (Bauer et al, 2006;Lobmaier et al, 2012) long (lAMP) SD: SDNN -standard deviation of NN intervals (TaskForce, 1996) TP: total power, VLF: very low frequency p., LF: low frequency p. (David et al, 2007) Amp: 20-95 inter-quantile range of NN intervals STV: mean difference between consecutive NN interval epochs of 3.75s, w/o DC, artifacts <50%, the parameter is referred to as STV -'short term variation' in the literature owing to the temporal resolution constrains of cardiotocography (Pardey et al, 2002) LTV: "long-term variation", mean fluctuation range of NN epochs in 1 min sections w/o DC, artifacts < 50%, part of the dataset referred to as the Dawes-Redman-criteria (Pardey et al, 2002) DCsl4, DCst4, ACsl4, ACst4, slope and step values across the change at a coarse graining level of 4 NN intervals (long) see above COMP: Complexity: indices of irregularity, invers to predictability. Complexity is a characteristic that is per definition independent of the amplitude of a signal.…”
Section: Figures Without Legendmentioning
confidence: 99%
“…Thus, nonlinear measures seem more consistent to reflect the prenatal developmental factors influencing cardiovascular regulation [7]. A nonlinear analysis, known as symbolic dynamics (SD), has also been employed to quantify fetal heart rate fluctuations during pregnancy, demonstrating that the use of this technique appears to provide a better and more differentiated understanding of healthy-physiological fetal development [8,9,10,11]. Some studies have confirmed that SD can be a helpful analysis to classify fHRV [6] and to evaluate the individual fetal gestational progress during pregnancy [9].…”
Section: Introductionmentioning
confidence: 99%